The convergence and synchronization of business cycles in the European Union and the European Monetary Union - Borowiec, Jan (Konwergencja i synchronizacja cykli koniunkturalnych w Unii Europejskiej oraz unii gospodarczej i walutowej, 2020)
The main aim of the paper is to determine the similarities and differences in the convergence and synchronization of business cycles in the EU and EMU in 1995-2018. The secondary goals are the following: a) the identification of the core and peripheries of European business cycles; b) the effects of monetary integration and the level of economic development and scale of the economy on the convergence and synchronization of business cycles. The results from the descriptive statistics and the correlation and regression analyses are: 1) classical cycles have a relatively high and similar concordance with the EU and the EMU, while at the same time they are strongly divergent on recession; 2) synchronization of the growth cycles is more diversified than classical cycles; 3) there is a clear division between the core and peripheries of European business cycles; 4) convergence of cycles is much more diversified than their synchronization; 5) level of economic development and the scale of the economy have an important influence on the convergence and synchronization of business cycles
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2020; vol. 64, nr 3, s. 7-20
Keywords: business cycles synchronization; cyclical convergence; international economic integration; European Monetary Union; synchronizacja cykli koniunkturalnych; konwergencja cykliczna; międzynarodowa integracja gospodarcza; europejska unia walutowa